Resource competition and ageism: a study of the influence of employment scarcity on the endorsement of ageist attitudes - Ospina, Javier H., author; Cleveland, Jeanette, advisor; Gibbons, Alyssa, committee member; Henle, Chris, committee member; Swaim, Randall, committee member (Colorado State University. Libraries, 2015)
The major economic recession of 2007, which has disproportionately affected younger workers, and the rapid growth of the older population have created an environment where younger persons are economically disenfranchised and a highly visible older population persists in the labor force at a time when jobs are scarce. Intergenerational conflict may arise under these conditions due to perceived competition over economic resources, consistent with Realistic Group Conflict Theory, which posits that negative intergroup perceptions arise when the success of one group is threatened by another, potentially leading to intergroup hostility. Younger workers may perceive older workers as a threat to their economic well-being and thus harbor ageist perceptions about them. To test this hypothesis, survey data was collected from 395 participants using Amazon's Mechanical Turk. The survey collected information about current employment status, duration of longest unemployment, number of peers unemployed, underemployment, job insecurity, and endorsement of ageist beliefs. Work centrality was investigated as a potential moderator for these relationships and perception of threat felt from older persons as a potential mediator. Results indicated that underemployment and job insecurity were both significant predictors of ageism. Workers who experienced greater underemployment or job insecurity were more likely to harbor ageist beliefs. Additionally, work centrality moderated relationships between peer unemployment and ageism, and perception of threat from older persons mediated relationships between underemployment/job insecurity and ageism. This study provides insight into how perceptions of age are influenced by economic factors and how a vulnerable group in society is affected during periods of economic turmoil.
Keywords: job insecurity; older workers; unemployment; Mechanical Turk; ageism; underemployment